Supply-side review of the UK specialist housing market and why it is failing older people. Issue 2 (14th September 2018) - Harding, Andrew; Parker, Jonathan; Hean, Sarah; Hemingway, Ann
Abstract : Purpose: The purpose of this paper is to provide a supply-side review of policies and practices that impact on the shortage of supply in the contemporary specialist housing market for older people in the UK. Design/methodology/approach: The review is based on a review of academic literature, policy documents, reports and other sources. Findings: There is a critical conflict between the key social purpose of specialist housing (i.e. living independent of socially provided care) and the values that underpin and ultimately limit the quantity of units in both the social and private sector. In the social sector, government policies prohibit rather than encourage local authorities and housing associations from increasing specialist housing stock. The nature of leasehold tenures in the private sector tends to commodify not only housing stock but also those who use it and therefore acts to instrumentalise housing supply in favour of the profit motive and the focus on the person and her or his needs is largely ignored. Originality/value: While the shortage of specialist housing is well known, this paper is unique in that it provides a comprehensive and critical supply-side review of the factors that have created such conditions.